PENERAPAN PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILANPASAL 22 ATAS PENGADAAN BARANG IMPOR - Mia Amelia Wahyuni; Mekar Meilisa Amalia; Rizkia Daulay (Worksheet : Jurnal Akuntansi, 2023)
The study aims to analyze the application of the calculation and reporting of income tax article 22 onthe procurement of imported goods at PT. Wicaksana Sentra Linkindo. The data used in this research isquantitative derived from secondary data in the period 2016 - 2018 with a descriptive approach anddata collection techniques through interviews and documentation. The results of the study show that thecompany has implemented the calculation and reporting of income tax article 22 according to the ratesstated in the tax regulations for chain products and generators. But in terms of collecting income taxarticle 22 on the procurement of goods with pump purchase partners it has not been properlyimplemented in accordance with PMK Number 34/PMK.010/2017.